2022
DOI: 10.1111/bcp.15429
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for vancomycin‐associated acute kidney injury: A systematic review and meta‐analysis

Abstract: and obesity (OR 1.46, 95% CI: 1.12-1.90) were associated with an increase in vancomycin-associated AKIs. In terms of vancomycin-related factors, longer treatment duration (>14 d; OR 1.73, 95% CI: 1.06-2.83), serum vancomycin trough level >15 μg/mL (OR 2.10, 95% CI: 1.43-3.07) and vancomycin trough level >20 μg/mL (OR 2.84, 95% CI: 1.48-5.44) increased the risks of vancomycin-associated AKI. For comorbidities and clinical factors, renal disease (OR 2.19, 95% CI: 1.51-3.17) showed the highest odds of vancomycin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 98 publications
1
8
0
2
Order By: Relevance
“…The use of loop diuretics also significantly increases the risk of VA-AKI, consistent with previous findings [ 7 ]. Prerenal factors lead to inadequate renal perfusion by decreasing the body's effective circulating blood volume, consequently resulting in AKI [ 16 – 18 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The use of loop diuretics also significantly increases the risk of VA-AKI, consistent with previous findings [ 7 ]. Prerenal factors lead to inadequate renal perfusion by decreasing the body's effective circulating blood volume, consequently resulting in AKI [ 16 – 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…Previous reports have shown that the incidence of VAN-associated AKI (VA-AKI) varies widely among different patient groups, ranging from 5 to 43% [ 6 ]. A meta-study discovered that independent risk factors for VAN-related nephrotoxicity included VAN serum trough concentrations, treatment duration and intensive care unit (ICU) stay, and concomitant use of nephrotoxic medications (acyclovir, aminoglycosides, amphotericin B, loop diuretics, piperacillin-tazobactam and vasopressor medications) [ 7 ]. Diabetes mellitus, heart disease, liver disease, kidney disease and sepsis can also contribute to kidney damage [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rates of AKI in our patients with MRSA (3.6%) were higher than the reported rates of AKI in 1 to 1.4% of patients in another study when vancomycin AUC was limited to less than 600 [ 19 ]. A higher rate of poly-microbial infections in the MRSA group, which resulted in concomitant piperacillin–tazobactam use, may have contributed to inflating the rate of AKI in our study [ 26 , 27 , 28 , 29 , 30 ]. Interestingly, regarding acute kidney injury rates, in studies involving non-MRSA or non-serious MRSA, significantly higher rates have been reported for patients with non-MRSA compared to patients with MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…One advantage of vancomycin is its effectiveness against methicillin-resistant staphylococci, and for that reason, Triffault-Fillit et al 23 recommended vancomycin as empirical therapy to cover methicillin-resistant coagulasenegative staphylococci in PJI patients. On the other hand, disadvantages of vancomycin are the high risk of complications, such as acute kidney injury 27 and its potentially inferior effectiveness against methicillin-sensitive S. aureus. 28,29 Vancomycin treatment also needs therapeutic drug monitoring.…”
Section: Discussionmentioning
confidence: 99%